Penelusuran Minat Bakat pada Siswa SMP dengan Menggunakan Aplikasi Screening Berbasis Web - Darwis, Muhammad; Wulandari, Devi; Hendrowati, Retno; Putri, Wahyuningdiah Trisari Harsanti; Putri, Sofia Tri; Fatih, Muhammad Adillah; Maulana, Reza Arif; Salsabilah, Ghina; Lestari, Maya Gita (Abdimas Mandalika, 2026)
Abstract:  This community service program aims to assist schools in identifying students’ interests and talents more quickly and efficiently through the development of a web-based screening application. The activity was conducted at SMK PKP Cibubur, targeting junior high school students as prospective applicants. The implementation of this program consisted of several stages, including joint planning with partners, needs analysis, instrument design based on the Rothwell Miller Interest Blank (RMIB), application design and development using Moodle with PHP and MySQL, user training, screening implementation, as well as evaluation and data processing. The results show that the developed application facilitates the online assessment of students’ interests and talents, allowing participants to obtain results immediately after completing the test. The program involved 378 students and was carried out successfully. Based on the evaluation results, user acceptance reached an average of 72%, categorized as “agree,” while the school expressed high satisfaction due to the faster, easier, and more efficient process without requiring significant resources. Therefore, the web-based screening application in this program effectively supports the process of identifying students’ interests and providing appropriate major recommendations.Abstrak: Program pengabdian kepada masyarakat ini bertujuan untuk membantu sekolah dalam menelusuri minat dan bakat siswa dengan lebih cepat dan efisien melalui pengembangan aplikasi screening berbasis web. Kegiatan dilaksanakan di SMK PKP Cibubur dengan sasaran siswa SMP sebagai calon peserta didik. Pelaksanaan PKM ini dilakukan meliputi beberapa tahapan, yaitu perencanaan bersama mitra, analisis kebutuhan, perancangan instrumen berbasis Rothwell Miller Interest Blank (RMIB), perancangan dan implementasi aplikasi menggunakan Moodle berbasis PHP dan MySQL, pelatihan pengguna, pelaksanaan screening, serta evaluasi dan pengolahan data. Hasil pengabdian menunjukkan bahwa aplikasi yang dikembangkan mampu mempermudah proses penelusuran minat bakat secara daring dengan hasil yang dapat diperoleh secara langsung oleh peserta. Kegiatan diikuti oleh 378 siswa dan berjalan dengan baik. Berdasarkan hasil evaluasi, tingkat penerimaan pengguna mencapai rata-rata 72% dengan kategori setuju, serta pihak sekolah menyatakan sangat puas karena proses menjadi lebih cepat, mudah, dan efisien tanpa membutuhkan banyak sumber daya. Dengan demikian, aplikasi screening berbasis web dalam PKM ini efektif mendukung proses penentuan minat dan rekomendasi jurusan siswa.